Editorial: Introduction to the Themed Issue of Adult Education and Sustainability - Sumner, Jennifer; Dobrich, Emily (The Canadian Journal for the Study of Adult Education / La revue canadienne pour l’étude de l’éducation des adultes, 2026)
As humans on a finite planet, we are facing an interconnected set of existential issues: climate change, war, displacement, and widespread precarity. Within this context, sustainability may appear a distant goal that we will never reach. However, the history of adult education shows that adults continue to learn, even in the face of great adversity. Learning sustainability involves a pedagogy of hope that calls on all of us to become both educators and learners, working together toward a more sustainable world.